ETHNOMATHEMATICS EXPLORATION IN THE PED’OA TRADITIONAL DANCE OF THE SABU COMMUNITY IN THE RAIJUA DISTRICT - Wiri, Paul Erikson Wada; Dominikus, Wara Sabon; Udil, Patrisius Afrisno (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2023)
Ped'oa is a traditional dance performed in mass by the Sabu community in a circle and led by the dance leader or mone pedjoe. This research aims to explore ethnomathematics in the Ped’oa traditional dance of the Sabu Community in the Raijua District. In addition, through ethnomathematics exploration, we can identify various mathematical concepts that exist in the Ped'oa traditional dance of the Sabu community in the Sabu Raijua Regency. This research is qualitative-explorative research with an ethnographic design. The subject of this study consisted of five people who were dancers and leaders of the cultural society. The data in this research is obtained through interviews, observations, and documentation. The data validity test is carried out by triangulation of sources. The data obtained were analyzed using Spradley's model data analysis techniques carried out through domain, taxonomy, componential, and cultural themes analysis. The results of this study showed that there is ethnomathematics in the Ped’oa traditional dance which is indicated by the characteristic of counting, locating, designing, and explaining activities. Based on those activities, mathematical concepts can be identified in the Ped’oa traditional dance, including multiplication, geometry, number patterns, geometric transformations, and mathematical logic. Those various mathematical concepts can be developed by designing mathematics learning tools that can be applied in mathematics learning, both for primary and secondary education levels